Migration, migrants, and the United States - Zaman, Niaz.; Ahmed, Kamal Uddin, 1941-; Bangladesh Association for American Studies (Dhaka, Bangladesh : Bangladesh Association for American Studies, 1992)
Papers presented at a conference organized by Bangladesh Association for American Studies, September 28, 1991.
Includes bibliographical references.
Keywords: Immigrants -- United States -- Congresses; Immigrants in literature -- Congresses; American literature -- History and criticism -- Congresses; United States -- Emigration and immigration -- Congresses